Development priorities in North -East India / edited by Bimal J.Deb - Deb, Bimal J. (ed.) (New Delhi, 2002)
There can be no two opinions about the fact that special category status of North Eastern states by itself failed to generate any worthwhile development and as a result the region continues to remain in the vortex of backwardness. It is against this background that the new development initiatives ought to be taken into account. What is, however, urgently needed is to set forth an agenda for development outlining the priorities so that concerted efforts could be set in motion to achieve the objectives. Hard decisions are indeed needed to tackle misdirected efforts and this calls for creation of a congenial atmosphere for investment and entrepreneurial activity. This book provides an indepth analysis of the core issues that require immediate attention of planners and administrators.
Keywords: Economic development-North East India